Pendampingan Aspek Pemasaran dan Keuangan pada IKM Seni Meubel Desa Kacongan Kabupaten Sumenep - Aprilya Dwi Yandari; Astri Furqani; Dina Kurniawati; Dessy Novita Laras Asih; Isnani Yuli Andini (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Based on the lack of understanding related to a good marketing system, how to record good financial statements, and their lack of analyzing the existing market analysis. So the service team tries to provide assistance related to the marketing and financial aspects by having a goal where IKM actors are able to market their products well by analyzing existing competitors by looking at market share. So that with this service, it is expected to be able to help SMEs to market and manage their finances well. The service method is carried out by conducting a survey first, pre-research, carrying out service, as well as an independent training process that is carried out at the final stage. Therefore, the owners and workers of the IKM are very active when the material is given and active at the application stage so that they understand and are able to deal with market conditions. This is very helpful for SMEs to determine the cost of goods, the purchase price of materials, and the selling price that is feasible to be marketed and become competitors for the same business actors.